Executive Function After Yoga: Adults With Acquired Brain Injury—A Pilot Study. - Grieb, Emily J.; Schmid, Arlene A.; Riggs, Nathaniel R.; Stephens, Jaclyn A. (American Journal of Occupational Therapy)
Importance: Acquired brain injury (ABI) may result in deficits in executive function (EF), which affects engagement in occupations. Objective: To explore the impact of group yoga on EF in people with ABI. Design: Single-arm pilot study with preyoga assessments and postyoga assessments (after 8 wk of yoga). Setting: Yoga classes and assessments were completed within university buildings on a college campus. Participants: Twelve participants with chronic ABI (>6 mo post-ABI) were recruited through convenience and purposive strategies from the local community. Intervention: An 8-wk adaptive group yoga intervention was provided by an adaptive yoga specialist. Yoga classes were 60 min and occurred once per week. Outcomes and Measures: EF was assessed before and after the yoga intervention using the Behavior Rating Inventory of Executive Function—Adult Version (BRIEF–A) self-report form. Normative data were analyzed with paired sample t tests. Results: Nine participants completed all study procedures. Results from paired sample t tests showed significant improvements on the Behavioral Regulation Index of the BRIEF–A (p =.046). No significant improvements were found on individual EF scales, the Metacognition Index, or the Global Executive Composite (ps >.05). Conclusions and Relevance: Group-based yoga may improve some aspects of EF for adults with chronic ABI; however, further research with larger sample sizes is needed. Plain-Language Summary: Yoga, an intervention increasingly used in occupational therapy practice, may be beneficial in improving behavioral regulation (an executive function) for adults with acquired brain injury. Group yoga may improve behavioral regulation for adults with acquired brain injury.